2021
DOI: 10.1002/lsm.23459
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of low‐energy carbon dioxide fractional laser use in the treatment of early‐stage pediatric hypertrophic scars: A prospective, randomized, split‐scar study

Abstract: Background: Various laser therapies have been introduced in scar management. However, pain during treatment has limited the application of laser therapy in pediatrics.Objectives: To evaluate whether the use of the low-energy mode of a carbon dioxide (CO 2 ) laser improves hypertrophic scars in a pediatric population. Methods: This prospective, randomized, split-scar trial was designed to assess the safety and efficacy of low-energy CO 2 laser use. Patients aged <12 years with hypertrophic scars were enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A total of 945 literature was retrieved through database retrieval, of which 75 replication studies as well as 345 systematic reviews, case reports and other studies were excluded. Studies without clear diagnostic criteria and no comparative data before and after treatment were excluded, and 10 pieces of literature were finally included for Meta-analysis [17][18][19][20][21][22][23][24][25][26] (Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 945 literature was retrieved through database retrieval, of which 75 replication studies as well as 345 systematic reviews, case reports and other studies were excluded. Studies without clear diagnostic criteria and no comparative data before and after treatment were excluded, and 10 pieces of literature were finally included for Meta-analysis [17][18][19][20][21][22][23][24][25][26] (Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Won et al 29 found low-energy CO 2 fractional laser therapy improved POSAS scores of hypertrophic scars in children. 29 A retrospective study of 221 hypertrophic scars patients found significantly decreased VSS scores after fractional laser treatment. 30 Several mechanisms lie behind the success of fractional CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…El‐Zawahry et al 28 found hypertrophic scars showed textural improvement and a significant decrease of VSS and POSAS scores after three fractional CO 2 laser sessions. Won et al 29 found low‐energy CO 2 fractional laser therapy improved POSAS scores of hypertrophic scars in children 29 . A retrospective study of 221 hypertrophic scars patients found significantly decreased VSS scores after fractional laser treatment 30 …”
Section: Discussionmentioning
confidence: 99%
“…13,14 Early treatment to prevent hypertrophic scar formation has been the main point of view in recent years. 15,16 Generally, CO 2 fractional laser therapy for scars has been applied at least 2 to 3 months after the surgery because scars are stable at this phase. 17 A recent study showed that early intervention with CO 2 fractional laser treatment significantly reduced scar formation less than 3 months after injury.…”
Section: Discussionmentioning
confidence: 99%